1994
DOI: 10.1083/jcb.125.6.1289
|View full text |Cite
|
Sign up to set email alerts
|

The Schizosaccharomyces pombe cdc3+ gene encodes a profilin essential for cytokinesis.

Abstract: Abstract. The fission yeast Schizosaccharomyces pombe divides by medial fission and, like many higher eukaryotic cells, requires the function of an F-actin contractile ring for cytokinesis. In S. pombe, a class of cdc-mutants defective for cytokinesis, but not for DNA replication, mitosis, or septum synthesis, have been identified. In this paper, we present the characterization of one of these mutants, cdc3-124. Temperature shift experiments reveal that mutants in cdc3 are incapable of forming an F-actin contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
217
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(235 citation statements)
references
References 37 publications
17
217
0
1
Order By: Relevance
“…Previous studies showed diverse cellular effects of overexpressed or microinjected Pfn1, where in some cases an increase in the overall F-actin content was noticed (Finkel et al, 1994) and in others depolymerisation of existing actin filaments occurred (as could be expected from its G-actin-sequestering property - Balasubramanian et al, 1994). This demonstrates the complexity and cell-type specificity of Pfn1's action on actin cytoskeleton.…”
Section: Pfn1 Overexpression Reorganises Actin Cytoskeleton and Upregmentioning
confidence: 69%
“…Previous studies showed diverse cellular effects of overexpressed or microinjected Pfn1, where in some cases an increase in the overall F-actin content was noticed (Finkel et al, 1994) and in others depolymerisation of existing actin filaments occurred (as could be expected from its G-actin-sequestering property - Balasubramanian et al, 1994). This demonstrates the complexity and cell-type specificity of Pfn1's action on actin cytoskeleton.…”
Section: Pfn1 Overexpression Reorganises Actin Cytoskeleton and Upregmentioning
confidence: 69%
“…h Ϫ cdc3-6 P. Nurse (Nurse et al, 1976;Balasubramanian et al, 1994 (Chang et al, 1997;Eng et al, 1998) Bähler and Pringle, 1998 JB23 h Ϫ cdc14-118 leu1-32 P. Nurse (Nurse et al, 1976) (Minet et al, 1979) Hiraoka et al, 1984 a Derived by mating two haploid strains obtained from J. Kohli. b myo2-E1 was originally referred to as rng5-E1 (Balasubramanian et al, 1998;Eng et al, 1998).…”
Section: Jb24mentioning
confidence: 99%
“…Thus, both Ain1p-GFP and GFP-Ain1p appear to provide normal Ain1p function. et al, 1976; McCollum et al, 1995) JB24 h Ϫ cdc3-6 P. Nurse (Nurse et al, 1976;Balasubramanian et al, 1994…”
Section: Molecular Biology Of the Cell 1062mentioning
confidence: 99%
See 1 more Smart Citation
“…Convincing arguments can be made for an in vivo role as an inhibitor [13][14][15], or stimulator [8,16] of actin polymerization. Indeed, it is entirely likely that profilin could be playing both roles, depending on species, cell type, or temporal regulation within an individual cell.…”
mentioning
confidence: 99%